Relationship between ultrasonographic and histopathological measurements of small intestinal wall layers in fresh cat cadavers. (July 2018) - Martinez, M.; Pallares, F.J.; Soler, M.; Agut, A.
Highlights: This study compared ultrasonographic to histologic small intestinal wall measurements in cats. There was good agreement for the total wall thickness and for most layers of small intestinal segments. The agreement for submucosa and muscularis measurements between both methods was poor. Ultrasonographic intestinal wall thickness measurements may serve as reference to detect pathologies in cats. Abstract: The relationship between histological and ultrasonographic thickness of the intestinal wall and its layers in cats is unknown so far. The aims of this study were to establish the relationship between ultrasonographic measurements in the transverse and longitudinal planes of the small intestine and to establish the agreement between ultrasonographic and histologic thickness of the overall intestinal wall and layers in cat cadavers. Seventeen adult cats were euthanased for reasons unrelated to gastrointestinal tract disease and ultrasonography was performed immediately after death using a high-frequency linear transducer. Ultrasound images of the duodenum, jejunum, ileum, and distal ileum were acquired in both the longitudinal and transverse planes. Small intestinal samples were collected close to where ultrasonographic images were obtained, fixed in formalin, and histological sections were obtained. Measurements of the intestinal layers and the overall wall thickness were performed on the ultrasonographic images and histological sections. No statistical differences were found between the ultrasonographic measurements of thickness obtained in the transverse and longitudinal planes except for the distal ileum ( P < 0.05). There was good agreement between the ultrasonographic and histologic measurements of the overall wall thickness and the layers of the different intestinal segments except at the submucosa and muscularis of the duodenum. Immediate postmortem ultrasonographic and histological thickness measurements of the different layers of the small intestine obtained in this study could serve as a reference for ultrasonographic scans and histological samples in cats.